THE ROLE OF THE DIGITAL ECONOMY IN THE DEVELOPMENT OF HUMAN CAPITAL IN THE LABOR MARKET MEASURES THROUGH THE RESOURCES AND ENVIRONMENTAL RESOURCES GRADUATES (International Journal of Scientific Research and Management (IJSRM), 2023)
The aim of clarifying the influence of the digital economy on the development of human capital in the labor market measured through graduates in the environmental industry. The author of the article deploys a survey questionaire for 165 new graduates of environmental majors in Hanoi. By quantitative linear regression research method on SPSS 20 software, the study has identified 5 factors of the digital economy that have an impact on the development of human capital of environmental graduates, including: (i) Operation of equipment and software (OES), (ii) Creation of information and data (CID), (iii) Communication and cooperation (CC), (iv) Creation of digital content (CDC), (v) Problem solving (PS), in which, the variables of OES, CID, CC, CDC have a positive relationship with the development of human capital, while the variable value of knowledge has a positive relationship with the development of human capital, while the variable CC has a negative relationship. Implications for managers, it’s necessary to develop and set up a digital system in universities and businesses in order to improve human capital, contributing to stable and sustainable development.